Partnership-based business mentoring: Dairy UMKM's collaboration with online couriers - Maulani, Denia; Agung, Syahrum; Komalasari (Jurnal Pengabdian Nusantara, 2023)
By analyzing the growth of dairy cattle farming enterprises during the COVID-19 pandemic with online courier partnerships, this service activity seeks to provide business aid through partnerships. The study was carried out at the Bogor district's kp. Bojong sempu using a qualitative methodology. A straightforward strategy for gathering data was used to interview and observe dairy milk MSME firm owners. Business actors, particularly dairy milk enterprises in kp. Bojong sempu, must be ready to face marketing challenges given the current state of the COVID-19 epidemic. Collaboration with dairy milk MSMEs through alliances with online couriers is one approach that might be taken. assistance in establishing dairy farming enterprises Using the available resources, dairy MSMEs in Bojong Sempu Village must increase production capacity while preserving and improving the quality of fresh milk. This includes marketing and distribution of products that must be sent more quickly without compromising the advantages and quality of products made from fresh cow's milk that consumers receive.